LUNG CANCER AS A COMORBIDITY OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Buklioska Ilievska, Daniela; Buklioska Adriana; Mickovski Ivana; Trajkova Vesna; Minov, Jordan; Stoleski, Sasho; Mijakoski, Dragan (My University, 2023)
COPD is a risk factor for lung cancer development independent of smoking status, with three to six times more likely to develop lung cancer at a rate of 0.8–1.7%/year. This may be associated with genetic susceptibility to cigarettes, chronic inflammation caused by toxic gases. Inflammatory mediators may promote the growth of bronchioalveolar stem cells, and activation of nuclear factor-κB and signal transducer and activator of transcription 3 play crucial roles in the development of lung cancer from COPD. The aim of the study is to evaluate the prevalence of lung cancer in patients with COPD. We performed a retrospective study, from 2012 to 2022, among patients with pathologically confirmed diagnosis of lung cancer, aged 40-75 years. Patients with lung cancer that had COPD diagnosed >= 10 years before lung cancer diagnosis, were investigated group. Histological subtypes of lung cancer were determined based on histopathology reports and were categorized as squamous carcinoma, adenocarcinoma, small cell lung cancer (SCLC), large cell lung cancer (LCLC; including large cell neuroendocrine carcinoma), and other histological types according to 2015 WHO classification of lung tumors. At the time of registration, sex, age, BMI, smoking status, treatment history, and symptoms, including the CAT score, were recorded. In addition, at the time of registration, spirometry was performed both before and after inhalation of a bronchodilator, and a blood test and chest CT were also performed. The GOLD criteria was used to diagnose and assign severity of COPD: patients with a postbronchodilator FEV1/FVC <0.70 were classified as having COPD; FEV1 ≥0.8 was defined as mild, 0.5≤ FEV1 <0.8 as moderate, 0.3≤ FEV1 <0.5 as severe, and FEV1 ≤0.3 as extremely severe. Patients were excluded if they presented with simultaneous or sequential second primary cancers or had a history of asthma, bronchiectasis, tuberculosis, pulmonary fibrosis, or other confounding diseases. The middle age of lung cancer diagnosis was 61.1±8.5 years. Of the total number of patients with COPD and lung cancer (260), 195 (75.0%) were male and 65 (25.0%) female. 190 (73.07%) were current smokers or ex-smokers. The histological subtypes identified were as follows: squamous carcinoma (96 [36.9%]), adenocarcinoma (115 [44.2%]), SCLC ( 26 [10.0%]), LCLC (13 [5.0%]), and other histologic types (including adenosquamous, carcinoma carcinoid tumors, sarcomatoid carcinoma; 16 [6.15%]). The proportion of squamous carcinoma was higher in smokers/ex smokers with COPD, while adenocarcinoma was more frequently observed in COPD non-smokers. Emphysema predominant phenotype was an independent prognostic risk factor for squamous carcinoma. The prevalence of COPD in lung cancer patients was 35.5%. Compared with lung cancer patients with non-COPD, those with COPD were older (P<0.001), had a lower BMI (P<0.001), and majority were male (P<0.001) and smokers (P<0.001). Annual low-dose computed tomography (LDCT) is an effective procedure for the early detection of lung cancer in high-risk patients like patients with COPD.
Keywords: COPD; lung cancer